Evaluation of Auditory Working Memory Abilities in Children with Self Limited Epilepsy with Centrotemporal Spikes (SECTS): A Pilot Study - Sreenivasan, Anuprasad; Krishna, Rajalakshmi; Nair, Pradeep Pankajakshan; Alexander, Arun (International Journal of Epilepsy, 2021)
Objectives Working memory abilities are essential in the perception of acoustic signals, especially in the presence of noise. This study aimed to measure the working memory and its associated factors in children with self-limited epilepsy with centrotemporal spikes (SECTS) and compare it with the typically developing children (TDC) without epilepsy.Materials and Methods Twenty-two children with SECTS and 22 typically developing children participated in the study. The Digit span backward test was used for measuring working memory abilities.Statistical Analysis and Results The working memory of children with SECTS, measured with backward digit span, was significantly poor compared with the TDC (p < 0.001). Factors such as the age of onset of seizures, duration of seizures, frequency of seizures and spike load did not influence the working memory.Conclusion The children with SECTS demonstrated impairment in working memory abilities compared with normal children. The association between poor working memory and reported speech recognition impairment in children with SECTS needs to be studied.
Keywords: self-limited epilepsy with centrotemporal spikes; working memory; digit span